(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: analyze the technologies available in the literature used for health education in the care of people with urinary incontinence. Methods: integrative review, with database searches: Índice Bibliográfico Espanhol de Ciências da Saúde (IBECS), Base de Dados em Enfermagem (BDENF) via Biblioteca Virtual em Saúde (BVS), Medical Literature Analysis and Retrieval System Online via Pubmed (MEDLINE/PubMed) from the National Library of Medicine, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Scopus, Web of Science and Embase. The collection was carried out in February 2021, with the main descriptors: Urinary Incontinence, Educational Technology and Health Education. Results: 91 articles were selected, after analyzing the inclusion and exclusion criteria, there were only 5 productions that were selected, presenting as a strategy the technologies: multimedia course, videos, mobile application and book/booklet. The articles were published between 1997 and 2020. The dimensions considered were: development of health technologies for the treatment of urinary incontinence and knowledge, adherence and the effect of using health technologies for the treatment of urinary incontinence. Conclusion: the technologies used were diversified, with the adherence and the effect being directly proportional, and it depends on how the individual understands urinary incontinence and the impact it brings on each person’s life.